2019
DOI: 10.1103/physrevb.99.174515
|View full text |Cite
|
Sign up to set email alerts
|

Gapless spin excitations in superconducting La2xCa1+xCu2O6 with

Abstract: We report inelastic neutron scattering on single crystals of the bilayer cuprate family La2−xCa1+xCu2O 6+δ , including two crystals made superconducting (transitions at 45 and 55 K) by high-pressure annealing in an oxygen-containing atmosphere. The magnetic excitations in the non-superconducting crystal have a similar temperature-dependence as those in weakly hole-doped cuprates. In the superconducting crystals, there is a near-uniform suppression of the magnetic spectral weight with increasing temperature; in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
(133 reference statements)
1
3
0
Order By: Relevance
“…In studies of antiferromagnetic spin fluctuations in La 2−x Ba x CuO 4 and La 2−x Sr x CuO 4 , Wagman et al [45,46] have identified evidence for spin-phonon coupling at energies in the range of 15-20 meV. We have observed a similar effect in our own samples of La 2−x Ba x CuO 4 [63] and La 2−x Sr x CuO 4 [64], and even in superconducting La 2−x Ca 1+x Cu 2 O 6 [65]. In most of these cases, the low-energy magnetic excitations have an incommensurate modulation, and it is possible that the coupling to phonons is related to that spatial variation.…”
Section: Spin Fluctuationssupporting
confidence: 82%
“…In studies of antiferromagnetic spin fluctuations in La 2−x Ba x CuO 4 and La 2−x Sr x CuO 4 , Wagman et al [45,46] have identified evidence for spin-phonon coupling at energies in the range of 15-20 meV. We have observed a similar effect in our own samples of La 2−x Ba x CuO 4 [63] and La 2−x Sr x CuO 4 [64], and even in superconducting La 2−x Ca 1+x Cu 2 O 6 [65]. In most of these cases, the low-energy magnetic excitations have an incommensurate modulation, and it is possible that the coupling to phonons is related to that spatial variation.…”
Section: Spin Fluctuationssupporting
confidence: 82%
“…For LSCO x = 0.17 and 0.21, it was observed that the spin gap is approximately equal to the coherent superconducting gap, ∆ c [313,314]. 34 This behavior has been observed in LSCO [281,305], YBCO [306,307], Bi 2 Sr 2 CaCu 2 O 8+δ [302], HgBa 2 CuO 4+δ [308,309], and La 2−x Ca 1+x Cu 2 O 6 [260]. 35 The dispersion in HgBa 2 CuO 4+δ has been characterized as having the form of a "wine glass" rather than an hourglass [308]; however, given the large damping, the data appear roughly consistent with a parabolic upward dispersion where the lower part of the dispersion is not resolved due to the damping.…”
Section: Role Of the Spin Gapmentioning
confidence: 67%
“…In an alternative direction, the 2D superconductivity in LBCO x = 0.115 can be pushed toward 3D order by suitable application of strain [258]. Going beyond single-layer cuprates, decoupling of superconducting bilayers in a c-axis magnetic field has been observed in crystals of La 2−x Ca 1+x Cu 2 O 6 with zero-field T c as high as 54 K [259]; stripe order has not been directly detected there, but the spin excitations remain gapless below T c [260].…”
Section: Superconducting Stripesmentioning
confidence: 99%
“…Inelastic neutron scattering measurements have been performed on a large crystal of the La-Ca-2126 x = 0.15 sample [38]. Although no static spin order was observed in association with the La-Ca-2126 phase, the bilayer magnetic excitations were found to be gapless, the latter being similar to the case of LBCO with x = 0.095 [39] and La 2−x Sr x CuO 4 with x = 0.07 [40], and suggestive of intertwined order [11].…”
Section: Discussionmentioning
confidence: 99%